Treatment of chlorobenzene contaminated wastewater using ozonation and anaerobic-aerobic systems - Khoeurn Kimleang (College of Engineering, University of the Philippines Diliman, 2013)
Chlorobenzene (CB) is one of benzene derivative compounds released into the environment. It has negative effects on aquatic life and human health such as cancer. Therefore, wastewater containing CB has to be treated before disposal. In this study, the performance of a series of ozonation (1 min at 0.3 g/h/2L), upflow anaerobic sludge blanket (UASB) reactor and aerobic processes for the degradation of chlorobenzene (CB) in synthetic wastewater (ca. 1700mg/L COD and 60 mg CB/L) was investigated at 24, 15 and 10 h hydraulic retention time (HRT) and compared to a similar anaerobic-aerobic process but without ozonation pretreatment and at the same HRTs for three months continuous runs. With prior one minute ozonation followed by 24 h UASB and 10 h aerobic treatment in series, the COD and CB removal were 98% and 98% respectively. At 15 h UASB and 6 h aerobic processes, the COD and CB removal were 91% and 96% respectively. In the process run at HRT 10 h UASB and 4 h aerobic treatment, the COD and CB removal were 82% and 88% respectively. The treatment processes at HRT 24 h UASB and 10 h aerobic in series achieved considerably high COD and CB removal efficiencies. However, with no prior ozonation, a 24 h HRT for UASB and 10 h aerobic treatment, the COD and CB removal were 88% and 89% respectively. At 10 h UASB and 4 h aerobic processes, 74% Cod and 62% CB removal efficiencies were obtained. The best process for CB removal at initial concentration of 60 ppm was with prior ozonation followed by aneorobic-aerobic process which significantly removed COD and CB Keywords: acetic acid, activated sludge, HRT, recalcitrant, UASB